2014
DOI: 10.1007/s10653-014-9605-8
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry, mineralogy, solid-phase fractionation and oral bioaccessibility of lead in urban soils of Lisbon

Abstract: An urban survey of Lisbon, the largest city in Portugal, was carried out to investigate its environmental burden, emphasizing metallic elements and their public health impacts. This paper examines the geochemistry of lead and its influence on human health data. A total of 51 soil samples were collected from urban recreational areas used by children to play outdoors. The semi-quantitative analysis of lead was carried out by inductively coupled plasma mass spectrometry after an acid digestion. X-ray diffraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 29 publications
3
29
0
Order By: Relevance
“…Therefore, a sub-set of eleven indoor dust samples corresponding to the exposed group was selected to carry out the bioaccessibility testing. In this study, bioaccessibility is defined as the concentration of metal extracted from dust in the G stage, which is the UBM stage that provides higher extracted concentrations (Reis et al 2014b) Since Mn in indoor dust samples is bioavailable to humans, the relationships between Mn contents in dusts and toenail clippings were further investigated using Pearson's product moment correlation coefficient (r). A paired sample t-test is used to establish the statistical significance of r that was considered at p< 0.01.…”
Section: Oral Bioaccessiblity Of Cu and Mn In Indoor Dust Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a sub-set of eleven indoor dust samples corresponding to the exposed group was selected to carry out the bioaccessibility testing. In this study, bioaccessibility is defined as the concentration of metal extracted from dust in the G stage, which is the UBM stage that provides higher extracted concentrations (Reis et al 2014b) Since Mn in indoor dust samples is bioavailable to humans, the relationships between Mn contents in dusts and toenail clippings were further investigated using Pearson's product moment correlation coefficient (r). A paired sample t-test is used to establish the statistical significance of r that was considered at p< 0.01.…”
Section: Oral Bioaccessiblity Of Cu and Mn In Indoor Dust Samplesmentioning
confidence: 99%
“…It has been demonstrated that bioaccessibility, and therefore bioavailability, depends on the chemical form of the contaminant (Rasmussen et al 2008;Demetriades et al 2010;Beauchemin et al 2011;Reis et al 2014b) and that the chemical form of the contaminant changes over time, usually resulting in a decreasing bioaccessibility (Tang et al 2008). But the ageing processes that are effective at outdoor removal of contaminants do not operate, or they operate at reduced efficiency, indoors compared to outdoors, because contaminants in indoor dusts are protected from sunlight, rain, temperature extremes, and microbial action, in particular dust trapped in carpets and drapes (Paustenbach et al 1997;Bierkens et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Over the years the emphasis has been on leaded fuel (Oudijk, 2010;Nriagu et al, 1996;Romieu et al, 1992), but there are many other activities that release Pb into the environment particularly in the urban/industrial setting: activities such as metal mining, smelting and processing, the use of Pb in lead-acid batteries, pigments, alloys, lead wool, chemical manufacturing, cables, solders, plumbing components, food cans, coal combustion, lead based paint (including that in road markings), and industrial waste (Ajmore-Marsan and Biasioli, 2010;Brown and Longoria, 2010;De Silva et al, 2016;Laidlaw and Taylor, 2011;Mielke et al, 2010;Shen et al, 2002). Studies have shown that the Pb retained in soil/dust because of anthropogenic activity typically occurs in highly bioavailable, exchangeable and carbonate forms, whereas, Pb retained because of natural occurrence is often found in residual or lessbioavailable forms (Chlopecka et al, 1997;Cox et al, 2013;Palumbo-Roe et al, 2013;Pelfrêne et al, 2012;Laidlaw and Filippelli, 2008;Reis et al, 2014;Ruby et al, 1994). Direct exposure to urban dust through inhalation is expected thus the respiratory tract is a potentially significant pathway through which urban dusts can enter the human body.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure no longer requires the chemistry of the reagents to be specific as this is now carried out mathematically by the chemometric analysis. Recent studies have shown the CISED to be a useful methodology for understanding the solid-phase fractionation of PTEs and its influence on their bioavailability (Cox et al, 2013;Palumbo-Roe et al, 2013;Reis et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, understanding factors that cause exposure of human population, and children in particular as the most vulnerable receptor, seemed of paramount importance. The present paper follows on from the earlier work of Cachada et al (2013) and Reis et al (2014b), utilising soil samples resulting from two similar environmental surveys carried out in the city of Lisbon. The main aim of the study herein described was performing a source-pathway-fate analysis of Pb and PAHs in urban soils that in their majority were collected from outdoor recreational areas, to increase current knowledge on their potential impacts on the health of the population.…”
Section: Introductionmentioning
confidence: 99%